Classificação de decisões judiciais sobre dados presentes no diário eletrônico da justiça do trabalho (DEJT) - Silva, Jonathan Santos (Universidade Federal de São Carlos, 2023)
Efficiently classifying legal decisions as approved or rejected is critical to ensuring a fair and effective justice system. This study presents a solution for this task, using machine learning techniques. The proposed solution involves data structuring, unit identification, labeling by experts, and training a machine learning model. O study included an exploratory analysis of source data and pre-processing techniques text for cleaning and normalizing the data. The proposed model achieved a rate high accuracy of 96%. Finally, we validate the model using external data and real cases. The results suggest that the model has the potential to be an effective solution for classifying legal decisions accurately and quickly.
Classification of court decisions on data present in the electronic diary of the justice of the work (DEJT)
Keywords: Data mining; Jurimetria; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO